Pajak Sebagai Sumber Pendapatan Negara (Analisis Sejarah Penentuan Kadar Pajak Di Masa Umar Bin Khattab Menurut Abu Yusuf dalam Kitab Al-Kharaj - Junaidi LBS (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2016)
Implementation of tax revenue to finance the country has been done by the Prophet’s companions since the time of Umar bin Khattab. Levies taken on the basis of their income which has met a certain amount, the amount must be equal to those who are eligible to pay zakat. Levels are levied based on the levels of zakat obligatory. For trade tax of 2.5% or l / 40, in 40 earnings taken one part of the country that will be used to finance operational tasks to build the country in all its forms. For the agricultural tax is measured by charity crops, which is l / 10 if naturally irrigated and l / 20 if irrigated using a tool, or 10% and 5%, in ten taken one and drawn one in 20. The obligation of the state is measured with the obligations of religion. Only the obligation of the state designated as operational funding and development of the country aimed at all the people, while liabilities towards religion designated as the fulfillment of consumer needs for the poor people.